2016
DOI: 10.1089/cap.2015.0130
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Satisfaction with a Multisite Trial of Atomoxetine and Parent Training for Attention-Deficit/Hyperactivity Disorder and Behavioral Noncompliance in Children with Autism Spectrum Disorder

Abstract: Objective: The purpose of this study was to examine caregiver satisfaction with the research experience in a randomized clinical trial of atomoxetine (ATX) and parent training (PT) for attention-deficit/hyperactivity disorder (ADHD) and behavioral noncompliance co-occurring with autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…However, there was a significant increase in early morning awakenings, which reportedly decreased after 12 weeks of open-label treatment (Harfterkamp et al 2012(Harfterkamp et al , 2013. In spite of this, both the CHART study and the Harfterkamp RCT found that ATX was generally well tolerated Harfterkamp et al 2012;Tumuluru et al 2017) and acceptable to participant families (Hollway et al 2016).…”
Section: Discussionmentioning
confidence: 98%
“…However, there was a significant increase in early morning awakenings, which reportedly decreased after 12 weeks of open-label treatment (Harfterkamp et al 2012(Harfterkamp et al , 2013. In spite of this, both the CHART study and the Harfterkamp RCT found that ATX was generally well tolerated Harfterkamp et al 2012;Tumuluru et al 2017) and acceptable to participant families (Hollway et al 2016).…”
Section: Discussionmentioning
confidence: 98%